Pemikiran Muhammad bin Sulaiman bin Saad Al-Kafiyaji dalam Bidang Sejarah: Studi Historiografi dan Filologi Terhadap Kitab Al-Mukhtas A-R Al-Mufid Fi Ilmi Al-Tarikh Abad ke-15 M - Nurcahya, Nurcahya; Akbar, Mahbub Hefdzil (Historia Madania: Jurnal Ilmu Sejarah, 2019)
Al-Kafiyaji was a popular folk teacher of his time and he also mastered quite a number of scientific branches and wrote many works especially in the field of history namely the book of Mukhtasar al-MufId fi Ilmi al-Tarikh. The purpose of this study aims to determine the biography and thoughts of al-Kafiyaji in the field of history based on the book of Mukhtasar al-Mufid fi Ilmi al-Tarikh. The method used in this study is a qualitative method, namely by collecting data through literature and documentation. The data analysis technique is done by the heuristic, criticism, interpretation and historiography methods. Based on this study it was concluded that: first, Muhammad bin Sulaiman bin Saad bin Mas'ud al-Rumi Muhyiddin Abu Abdillah al-Kafiyaji al-Barumi al-Hanafi was born around 788H / 1386/7 AD in the Anatolian Caucasus region located in the Asian region of Asia small and died in Egypt, and took the education world from the land of Sham to Egypt and produced many many works especially in the field of history. Secondly, in the field of history or Tarikh he has written the work entitled Mukhtasar al-Mufid fi Ilmi al-Tarikh. In this book, al-Kafiyaji examines the principles of historiography, the basics and the problems of historiography and the virtues of experts and sciences. He also investigated the date, from the definition based on language, custom, and terminology, to the history ofÂ  the Tarikh. This book discusses the goals and conditions that must be possessed by someone who will write history.